2020
DOI: 10.1016/j.celrep.2020.108288
|View full text |Cite
|
Sign up to set email alerts
|

Prdm16 Deficiency Leads to Age-Dependent Cardiac Hypertrophy, Adverse Remodeling, Mitochondrial Dysfunction, and Heart Failure

Abstract: Highlights d Prdm16 is dispensable for cardiac development d Prdm16 cKO mice develop hypertrophy, adverse remodeling, and mitochondrial dysfunction d Prdm16 cKO mice are predisposed to develop heart failure in response to metabolic stress d Prdm16 and Ehmts act together to repress expression of hypertrophic genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 78 publications
2
66
0
3
Order By: Relevance
“…These include i) three G protein coupled receptors, E2 (CD97), L3 (Latrophilin 3), and F5, encoded by Adgre2, Adgrl3 , and Adgrf5 , respectively; ii) the guanine nucleotide exchange factor, Dock9 , that activates Cdc42; iii) three GTPase activating proteins that are negative regulators of the GTPases Cdc42 and Rac1, namely Cdc42 GTPase-activating protein ( Cdgap or Arhgap31 ), Stard8 (Dlc2) 36 and Stard13 (Dlc3) 37 ; and iv) Cds2 (CDP-diacylglycerol synthase 2), which regulates the amount of phosphatidylinositol downstream of GPCR signaling by catalyzing the conversion of phosphatidic acid to CDP-diacylglycerol. The 13 th gene, Prdm16 , encodes a transcriptional regulator involved in brown fat metabolism, that has recently been shown to protect from cardiovascular aging 38 .…”
Section: Resultsmentioning
confidence: 99%
“…These include i) three G protein coupled receptors, E2 (CD97), L3 (Latrophilin 3), and F5, encoded by Adgre2, Adgrl3 , and Adgrf5 , respectively; ii) the guanine nucleotide exchange factor, Dock9 , that activates Cdc42; iii) three GTPase activating proteins that are negative regulators of the GTPases Cdc42 and Rac1, namely Cdc42 GTPase-activating protein ( Cdgap or Arhgap31 ), Stard8 (Dlc2) 36 and Stard13 (Dlc3) 37 ; and iv) Cds2 (CDP-diacylglycerol synthase 2), which regulates the amount of phosphatidylinositol downstream of GPCR signaling by catalyzing the conversion of phosphatidic acid to CDP-diacylglycerol. The 13 th gene, Prdm16 , encodes a transcriptional regulator involved in brown fat metabolism, that has recently been shown to protect from cardiovascular aging 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Heart failure is one of the most fatal cardiovascular diseases worldwide. 42 It is important to identify effective therapeutic targets that inhibit maladaptive hypertrophy and subsequent heart failure. In the present study, we found that lncRNA AAB was remarkably upregulated in cardiac hypertrophy rats and this upregulation promoted ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Роль PRDM16 широко изучалась в жировой ткани [15]. Одновременно с этим показана экспрессия PRDM16 в кардиомиоцитах мыши и человека [16,17].…”
Section: Discussionunclassified
“…Последующие исследования подтвердили роль вариантов, приводящих к утрате копии PRDM16, в развитии НМЛЖ и дилатационной КМП у детей [18]. В экспериментах на нокаутированных по гену PRDM16 мышах была показана роль PRDM16 в развитии гипертрофической КМП [17,19] [16], однако для однозначного вывода о связи этого гена с НМЛЖ и первичными КМП имеющихся данных недостаточно.…”
Section: Discussionunclassified